La Heliofanía y su relación directa con el desarrollo fenológico y fenométrico del cultivo de rosas en el Ecuador - Alucho Chimbo, Ángel Olmedo (2020)
The cultivation of roses currently has a great connotation in the country, since it has a very sustainable international market, being the generator of 0.72% of the national GDP and in turn allows a large amount of foreign currency. But it is necessary to indicate that nowadays there are several climatic factors that can generate adverse situations, such as: long periods of cloudiness, unstable variations in temperatures and outdated information on the behavior of solar luminosity. That is why this bibliographic research requires presenting possible solutions to provide reliable knowledge on the subject under study, which was based on first-level or high-impact studies, and in this way socialize adequate information regarding the importance of luminosity. solar and degree day development, therefore it is recommended to carry out more research on this crop, through experimentation with different types of roses; and in turn with greater updating and socialization of important data on agroclimatic factors, which fluctuate every year, in order to improve the problem raised as much as possible.